1999
DOI: 10.1128/iai.67.7.3580-3586.1999
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in the Pathogenesis of Avian Salmonellosis

Abstract: Salmonellae are gastrointestinal pathogens of man and animals. However, strains that are host-specific avian pathogens are often avirulent in mammals, and those which are nonspecific are commensal in poultry. The objective of this study was to determine whether host specificity was exhibited by bacterial abilities to invade epithelial cells or resist leukocyte killing. In this study, leukocytes isolated from humans and chickens were used to kill Salmonella in vitro. Both Salmonella pullorum, an avian-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(47 citation statements)
references
References 42 publications
3
39
1
4
Order By: Relevance
“…Shu-Xuan et al (2008) reported that quantitative studies of the regular distribution pattern for Salmonella Enteritidis in the internal organs of mice after oral challenge by a specific real-time polymerase chain reaction showed higher distribution in the liver and spleen. Salmonella organisms are known to replicate in the reticuloendothelial systems, while lymphoid tissues are targets for Salmonella invasion (Carter and Collins, 1974a and b;Henderson et al, 1999). It has been reported that Salmonella infection of lymphoid tissue can account for the depletion and necrosis of lymphoid follicles of the spleen seen in most Salmonella infections (Henderson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Shu-Xuan et al (2008) reported that quantitative studies of the regular distribution pattern for Salmonella Enteritidis in the internal organs of mice after oral challenge by a specific real-time polymerase chain reaction showed higher distribution in the liver and spleen. Salmonella organisms are known to replicate in the reticuloendothelial systems, while lymphoid tissues are targets for Salmonella invasion (Carter and Collins, 1974a and b;Henderson et al, 1999). It has been reported that Salmonella infection of lymphoid tissue can account for the depletion and necrosis of lymphoid follicles of the spleen seen in most Salmonella infections (Henderson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due, in part, because broilers typically have fewer numbers of mononuclear cells compared to other types of chickens [31]. It is also possible that the timing was not optimized for monitoring mononuclear migration into the abdominal cavity, since mononuclear cell migration does not peak until four days post-challenge [32] compared to 4 h post-challenge for heterophils. Henderson et al [32] also reported that macrophages were less efficient at killing various Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In case of inadequate body defense mechanism, they may lead to second invasion and be localized in other organs, particularly ovary, oviduct, myocardium, pericardium, gizzard, yolk sac and/or lungs [177]. In the bird challenge, S. typhimurium rapidly caused inflammation of the intestinal mucosa, but S. pullorum preferentially targeted the bursa of Fabricius prior to eliciting intestinal inflammation [178]. Pullorum disease manifests itself predominantly as an enteric disease of chickens, while fowl typhoid shows signs of septicemic disease [78].…”
Section: Pathogenesis and Disease Syndrome Of Avian Salmonellosismentioning
confidence: 99%